Elimination of temperature cross-sensitivity for polymer FBG-based humidity sensor by gamma radiation treatment - Chapalo, Ivan; Gusarov, Andreï I.; Chah, Karima; Ioannou, Andreas; Pospori, Andreas; Nan, Ying-Gang; Kalli, Kyriacos; Megret, Patrice (My University, 2023)
In this work, we investigate the influence of gamma radiation treatment on sensing properties of fiber Bragg gratings (FBGs) inscribed in polymer CYTOP fiber with line-by-line method and femtosecond laser pulses. Polymer FBGs are known to have a wider strain range and a stronger temperature sensitivity compared to silica FBGs. Also, they exhibit sensitivity to the relative humidity (RH) that is therefore an additional physical quantity possible to measure. However, in practical applications of RH sensing, temperature cross-sensitivity must be compensated. Irradiating CYTOP FBG samples with various doses (80, 160, 200, 280, and 520 kGy), we found that the gamma radiation treatment changes their climatic properties. Initially positive value of the temperature sensitivity (19.6 pm/℃) decreases with the received dose with subsequent change of the sign from positive to negative. This opens a possibility of making FBGs insensitive to temperature. Among the irradiated samples, the one received the dose of 200 kGy demonstrated the lowest temperature sensitivity (1.77 pm/℃). For higher dose (520-kGy), the sensitivity was found to be -38.9 pm/℃. Along with a decrease of temperature sensitivity, we observed an increase of RH sensitivity with the received dose from 13.3 pm/%RH for pristine FBG up to 56.8 pm/%RH for the case of 520 kGy dose. Thus, by correct selection of the irradiation dose, gamma irradiation of CYTOP FBGs is a promising pre-treatment technique to improve the RH sensitivity of CYTOP FBGs with eliminating the temperature effect.
Keywords: CYTOP; fiber Bragg gratings; fiber optic sensors; perfluorinated polymer; Polymer optical fiber